Effect of domestic cooking methods on the anthocyanins and antioxidant activity of deeply purple-fleshed sweetpotato GZ9 - Liao, Minghuan (Heliyon, 2019)
Purple-fleshed sweetpotatoes (PFSPs) are considered to be a healthy food and there are many methods to process in family. This study aimed to investigate the effects of various domestic cooking on the anthocyanin variation and antioxidant activity of a newly bred purple-fleshed cultivar Guangzishu 9 (GZ9) with anthocyanin content up to 1,500 mg/100g dry weight. As a result, total 15 individual anthocyanins were separated and identified by using UPLC-QTOF-MS. Top three anthocyanins were cyanidin 3-dicaffeoyl sophoroside-5-glucoside, cyanidin 3-caffeoyl- p-coumaryl sophoroside-5-glucoside and peonidin 3-caffeoyl-p-hydroxybenzoyl sophoroside-5-glucoside, which accounting for 57.27% of the total anthocyanin content. Acylated anthocyanins were the major constituents in GZ9, and the type of anthocyanins was dominated by cyanidin. Boiling, steaming and mircrowaving had no significant effect on the total anthocyanin content. But baking, frying, air-frying and stir-frying reduced 11–45% of total anthocyanin content. Through ABTS(+) radical scavenging capacity and reducing power, antioxidant variations were also observed during different family cooking, and the variation had a strong correlation with total anthocyanin content.